Health-related quality of life of students from a private medical school in Brazil - Lins, Liliane (Int J Med Educ, 2015)
OBJECTIVES: To assess health-related quality of life (HRQOL) and to describe factors associated with its variation among undergraduate medical students at a Brazilian private medical school. METHODS: A cross-sectional study in a sample (n=180) of medical students at a private medical school in Salvador, Brazil, stratified by year of medical course. Data about age, sex, year of course, physical activity, sleepiness, headaches, participation in a student loan program supported by the Brazilian government (FIES) and living arrangements were collected using a self-administered form. HRQOL was assessed by using a Brazilian Portuguese version of the SF-36 form. The eight domains of SF-36 and the Physical Component (PCS) and Mental Component (MCS) Summaries scales were calculated. RESULTS: The medical students showed poor HRQOL, mainly because of the mental component. Lower mean scores were found among those with FIES support, females, those suffering from sleepiness, headaches and lacking physical activity. No clear trend was observed in the variation of the SF-36 mean scores according to the year of medical school. However, students in the fifth year of the course had the highest HRQOL mean scores. CONCLUSIONS: Health-related quality of life of students at this private medical school was poor, mainly because of its mental component. Lower HRQOL was associated with FIES support, females, sleepiness, headaches and lack of regular physical activity. Higher scores were found among fifth year students.